2017
DOI: 10.2174/1874205x01711010084
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Hastens and Omega-6 Delays the Progression of Neuropathology in a Murine Model of Familial ALS

Abstract: Background:Amyotrophic lateral sclerosis (ALS) is a progressive disease of motor neurons that has no cure or effective treatment. Any approach that could sustain minor motor function during terminal stages would improve quality of life.Objective:We examined the impact of omega-3 (Ω-3) and Ω-6, on motor neuron function in mice expressing mutant human superoxide dismutase-1 (SOD-1), which dominantly confers familial ALS and induces a similar sequence of motor neuron decline and eventual death when expressed in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…For example, omega-3 supplementation in mouse models of ALS reported an increased cellular damage that could increase disease progression [ 120 ]. Similar results were obtained in a more recent study in a murine model of familial ALS [ 121 ]. However, combination of omega-3 and vitamin E could reduce ALS risks [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, omega-3 supplementation in mouse models of ALS reported an increased cellular damage that could increase disease progression [ 120 ]. Similar results were obtained in a more recent study in a murine model of familial ALS [ 121 ]. However, combination of omega-3 and vitamin E could reduce ALS risks [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Going against the common perception that Ω-3 fatty acids are "healthy" and Ω-6s are "unhealthy," we counterintuitively found that Ω-3 levels were elevated, and Ω-6 levels diminished, in individuals at high genetic risk for ALS. Supporting this association, Ω-6s delayed disease progression in a mouse model of ALS, while Ω-3 supplementation hastened progression (34), suggesting dietary modulation of Ω-3 and Ω-6 fatty acids may be a useful therapeutic strategy for ALS. [Conversely, an observational epidemiological study found an inverse correlation between Ω-3 intake and ALS risk, and a nonsignificant correlation with Ω-6 intake ( 57). ]…”
Section: Noncanonical Disease-analyte Associationsmentioning
confidence: 93%
“…The largely sporadic nature of most ALS cases indicates that extrinsic factors, including diet, may play a relevant role in ALS, representing either a potential risk or a neuroprotective factor [ 141 ]. Growing evidence demonstrates that specific nutritional regimens [ 142 ] or dietary components [ 143 ] may influence the state of ALS patients or mouse models, by affecting at several levels (microbiome, mitochondrial activity, etc.) the pathological condition of high oxidative stress.…”
Section: Noncoding Rna Landscapementioning
confidence: 99%